Aplicação da teoria comunicacional do direito no negócio jurídico - Esteves, Jean Soldi (2013)
This paper supports a new approach to juristic acts, as a kind of dispositive fact. The approach is based on the communication theory of law, establishing a brief parallel between the historical and current approach on juristic acts and the approach presented herein, by means of applying the communication theory. It is irrefutable that both theories had a substantial evolution in the last thirty years and also, it is evident that the same should be aligned based on the scientific relevance they have. On the other hand, it is important to highlight in the field of comparative law, the use of the communication theory of law, particularly in Spain, where its main founder, attorney Gregorio Robles, established a growing dialogue with Brazilian jurists concerning not only the conformation of such communication theory of law, but also, as a consequence, its application and impact on various areas of law. This paper supports not only its existence, validity and effectiveness, but also its full application in a new approach to the theory of juristic acts, thus providing a comparative study of the civil law. The research seeks to apply the theory of communication to matters concerning the cause and reason in juristic acts, proposing a methodological analysis from the semiotics‟ point of view, and its syntactic, semantic and pragmatic dimensions. In fact, according to the semiotics, terminology entails a specific investigation on the definition of the concept of cause and reason, as determinants of the juristic acts, associated to matters concerning declaration of intent. Based on the signifier figure (physical support), concerning the meaning (referent or external object) and significance (understanding, interpretation or legal rule), it can be noted that the juristic act reason corresponds to the psychic impulse that leads one person to actualize it at an emotional references (pleasure, satisfaction, delight someone close, reward) and the juristic act cause corresponds to its objective reasoning, i.e., an specific element, such as an investment, acquisition of a home, sale of a good. There is, therefore, an acknowledgment of the law as a communication phenomenon and every implication that it generates in the various branches of the law